Synthesis of New 2-Derivatives of 3-(5,6,7,8-Tetrahydronaphthalen-2-yl)Quinoxaline (Biological Sciences - PJSIR, 2005)
The known compound 3-(5,6,7,8-tetrahydronaphthalen 2-yl)-2-(1H)-quinoxalone was used to synthesize a new series of derivatives. Synthesis of a class of six quinoxaline derivatives, a new series of three hydrazinoquinoxaline-Schiff bases, and a corresponding Mannich base are described. The analytical data on the newly synthesized compounds reported in the paper include their melting points, percent yields, molecular formulae, molecular weights, and percent C, H, N calculated and experimental values. Also given are the IR, 1H NMR, and mass spectral data of these new compounds.